2018
DOI: 10.1186/s12885-018-4123-1
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis is essential for chemoresistance induced by transient receptor potential channel C5 in colorectal cancer

Abstract: BackgroundElevated intracellular Ca2+ ([Ca2+]i) level could lead to [Ca2+]i overload and promote apoptosis via different pathways. In our previously study, up-regulated expression of transient receptor potential canonical channel (TRPC5) was proven to increase [Ca2+]i level, and resulted in chemoresistance whereas not apoptosis in human colorectal cancer (CRC) cells. The ATP-dependent homeostatic maintenance of resting [Ca2+]i should be important in this process. Increased glycolysis was found to be an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Recently, studies report that chemoresistant cancer show high level of glycolysis. 24,25 However, the potential mechanism for illustrating the association between glycolysis and chemoresistance is still unclear. In the present study, we found that the oxaliplatin-resistant CRC cells consumed more amount of glucose and exhibited higher level of glycolysis compared to the routine CRC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, studies report that chemoresistant cancer show high level of glycolysis. 24,25 However, the potential mechanism for illustrating the association between glycolysis and chemoresistance is still unclear. In the present study, we found that the oxaliplatin-resistant CRC cells consumed more amount of glucose and exhibited higher level of glycolysis compared to the routine CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…We next evaluated the difference of glycolysis between HT29/R (SW480/R) cells and their parental HT29 (SW480) cells, because some studies have reported that glycolysis is essential for chemoresistance in some cancers. 24,25 As shown in Figure 2A, HT29/R and SW480/R cells consumed more amount of glucose compared to the HT29 and SW480 cells. Furthermore, we observed that HT29/R and SW480/R cells produced more amount of lactate compared to the HT29 and SW480 cells ( Figure 2B).…”
Section: Ht29/r and Sw480/r Cells Exhibit High Level Of Glycolysis Anmentioning
confidence: 96%
“…43 Moreover, ENO1 knockdown was found to reduce glycolysis, increase OXPHOS, and cause growth arrest. 44,45 Other studies have found increased aerobic glycolysis is important in maintaining chemo-resistance, and it has been hypothesised that glycolytically-derived ATP contributes to, among other things, drug inactivation and increased intracellular survival signalling. 46 The upregulation of the mitochondrial MICOS complex subunit MIC60 (IMMT) and mitochondrial 60kDa HSP suggests there may have been some mitochondrial damage/stress associated with the treatment -MIC60 is a core unit of MICOS, which regulates cristae morphology and protein transport; 47 while mitochondrial HSP60 maintains proteins in an unfolded state to enable transport across the inner mitochondrial membrane.…”
Section: Metabolic Changes (Glycolysis Lipid Metabolism Mitochondrimentioning
confidence: 99%
“…Studies have revealed that enhanced glycolysis is associated with aggressiveness and poor prognosis in multiple cancers [16][17][18]. Accumulating data have also indicated that elevated aerobic glycolysis in cancer cells is critical for chemoresistance [18][19][20]. Taken together, the diverse roles of aerobic glycolysis in cancer suggest that alterations in the glycolytic pathway may influence chemotherapy outcomes.…”
Section: Introductionmentioning
confidence: 99%